A Powerful Synthesis Strategy of Novel Non‐Symmetrical Camphor‐Based Guanidines. Issue 11 (24th March 2018) - Ortmeyer, Jochen; Schneider, Tobias; Flörke, Ulrich; Henkel, Gerald; Neuba, Adam
Abstract: A convenient synthesis strategy for chiral camphor‐based non‐symmetrical bis‐guanidines with different peralkylated units is presented. The modular synthetic pathway to the first C1 ‐symmetric guanidines enables the implementation of chirality together with steric and electronic asymmetry via a step by step guanidinisation of camphor bis‐amine. The described guanidines were characterized using 1 H and 13 C NMR spectroscopy, ESI mass spectrometry, elemental analysis and X‐ray crystallographic analysis. Abstract : The first chiral camphor‐based non‐symmetrical bis‐guanidines with different peralkylated units are described. For their synthesis, a "step by step" guanidinisation of camphor bis‐amine with Vilsmeier salts was used. This modular method opens the access to a new family of chiral guanidine compounds.